2020
DOI: 10.1166/jnn.2020.17669
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Electrospun Nanofibrous Mat Based on Essential Oils for Biomedical Applications

Abstract: Polyurethane (PU) nanofibers containing three different essential oils (teatree, cinnamon bark, clove) were produced by electrospinning method. Morphology of the electrospun nanofibrous was studied using Field Emission Scanning Electron Microscope (FE-SEM). We were studying to reveal that different concentration of essential oil display different mechanical properties for the nanofibrous mat. The antibacterial properties of the nanofibrous loaded with the essential oil were studied quantitatively and qualitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The major benefits of local drug delivery are the decrease of unwanted side effects and bringing down the chance of developing drug resistance in the long term. , Several studies have shown that electrospun mats and hydrogels can be studied for local drug delivery . Polymeric nanofibers have attained prominent attention for local cancer therapy due to porosity, large surface area, versatile surface modification, and high surface-to-volume ratio. , However, for drug delivery applications, several synthetic polymers, such as polycaprolactone (PCL), polyethylene oxide (PEO), polylactic acid (PLA), and polylactic- co -glycolic acid (PLGA), as well as their blends, have been utilized to make electrospun nanofibers. Polycaprolactone (PCL), one of the synthetic degradable polymers, has been extensively utilized in biomedical materials because of its biocompatibility and ability to undergo hydrolysis. …”
Section: Introductionmentioning
confidence: 99%
“…The major benefits of local drug delivery are the decrease of unwanted side effects and bringing down the chance of developing drug resistance in the long term. , Several studies have shown that electrospun mats and hydrogels can be studied for local drug delivery . Polymeric nanofibers have attained prominent attention for local cancer therapy due to porosity, large surface area, versatile surface modification, and high surface-to-volume ratio. , However, for drug delivery applications, several synthetic polymers, such as polycaprolactone (PCL), polyethylene oxide (PEO), polylactic acid (PLA), and polylactic- co -glycolic acid (PLGA), as well as their blends, have been utilized to make electrospun nanofibers. Polycaprolactone (PCL), one of the synthetic degradable polymers, has been extensively utilized in biomedical materials because of its biocompatibility and ability to undergo hydrolysis. …”
Section: Introductionmentioning
confidence: 99%
“…Provided that the TPU concentration (12.5 wt %) remains constant, EOs were added separately into the TPU solution at different concentrations (1,5,10,15,20,25 wt %), then left for 24 h under magnetic stirring. Table 1 summarizes the all-solution concentrations obtained for each essential oil.…”
Section: Fabrication Of Tpu/eo Scaffoldsmentioning
confidence: 99%
“…Similarly, they used tea-tree-oil-infused PU nanofibers, characterized by mechanical, CO 2 reduction, and antibacterial tests, to extend the shelf-life of tomatoes [24]. Besides tea tree oil, PU nanofibers containing cinnamon bark and clove oils were also fabricated, and the antimicrobial activities were examined [25]. Unlike polymer/essential oil blend electrospinning, they also attempted the adsorption of cinnamon oil on the activated carbon, then mixed it with a PU solution, and subsequently electrospun it to obtain a higher amount of oil in the composite nanofibers [26].…”
Section: Introductionmentioning
confidence: 99%
“…The remarkable properties of EOs have prompted its use as additives for the formulation of functional biocomposites, especially for food packaging and biomedical purposes. ,,, Still, the growing demand for new biomaterials and biopolymers from renewable resources is pushing the limits of materials design, leading to the development of greener alternatives. , Among others, poly­(lactic acid), chitosan, natural silk fibroin, gelatin, and starch are biopolymers that have been incorporated with EOs to obtain materials possessing antimicrobial activity. However, these often require harsh chemicals/additivesor complex or additional stepsfor polymer solubilization and processing.…”
Section: Introductionmentioning
confidence: 99%